2009
DOI: 10.4161/psb.4.12.9903
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of brassinosteroids interacting with multiple hormones

Abstract: These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 54 publications
0
29
1
Order By: Relevance
“…Recent work on wild-type tissues of various plants has provided multiple physiological and molecular links to support extensive interplay between the BR and GA signaling pathways (Zhang et al, 2009). Considering these findings and given the emerging role of GA as a bona fide immunity hormone (Robert-Seilaniantz et al, 2011), we sought to extend our analysis of the disease-promoting effect of BRs by scrutinizing potential BR-GA cross talk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work on wild-type tissues of various plants has provided multiple physiological and molecular links to support extensive interplay between the BR and GA signaling pathways (Zhang et al, 2009). Considering these findings and given the emerging role of GA as a bona fide immunity hormone (Robert-Seilaniantz et al, 2011), we sought to extend our analysis of the disease-promoting effect of BRs by scrutinizing potential BR-GA cross talk.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, rather than directly promoting pathogen fitness, hostproduced BRs may enhance susceptibility to P. graminicola by interfering with specific plant defense signaling pathways. In compliance with this concept, there is ample evidence demonstrating extensive interplay between BR and other small-molecule hormones (Zhang et al, 2009). For example, BR modulates the biosynthesis of ET (Hansen et al, 2009) and intimately interacts with cytokinins and auxin in regulating various developmental processes (Goda et al, 2004;Vert et al, 2008;Peleg et al, 2011;Vercruyssen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15]25,26 The interactions between auxin and cytokinin, 27 auxin and ABA, 28,29 auxin and SA, 23 auxin and JA, 21 ethylene and ABA, 30 ethylene and cytokinin, 31 and JA and SA, 32 are well investigated and have been proposed to work coordinately or antagonistically to regulate different plant responses. However, the exact molecular mechanisms underlying the similar and antagonistic responses of different hormones remain to be understood.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] Based on gene expression and genetic studies in loss-of-function mutants, several genes involved in common signaling pathways of two or more hormones have also been identified and extensive crosstalk and signal integration has been uncovered. [12][13][14][15] Various genetic analyses suggested that hormones work via distinct pathways to elicit their responses. 12 However, it has also been proposed that plant hormones regulate similar biological processes via different signaling pathways.…”
Section: Introductionmentioning
confidence: 99%